Adaptive control with unknown mass estimation for a quadrotor-slung-load system. (February 2023) - Yu, Gan; Xie, Wei; Cabecinhas, David; Cunha, Rita; Silvestre, Carlos
Abstract: In aerial load transportation applications, knowing the mass of the load in advance is not always possible. The load dynamics depend on its mass and using a high-performance model-based controller with an inaccurate mass will introduce unmodeled disturbances to the system that will negatively affect the closed-loop performance. This paper addresses the design of a trajectory tracking controller for a quadrotor with a slung-load that has an unknown mass. The proposed solution is an adaptive controller with online estimation designed using the backstepping technique. Nonlinear control laws for thrust and angular velocity, and an adaption law for mass estimation are proposed, which guarantee the convergence of the trajectory tracking and the estimation errors to zero, and are robust to variations in load mass. Simulation and experimental results are presented to assess the validity and performance of the proposed controller. Highlights: A rigorous stability proof shows that the trajectory tracking and estimation errors converge asymptotically to zero. The adaption law is updated online, compensating the unknown mass while the load tracks a reference trajectory. The swing motion of the load is allowed to follow naturally the aggressiveness of the reference trajectory. High-performance experimental results are showcased, including trajectory tracking and aggressive maneuvers with varying load mass and large load swings.